A novel role for the fibrinogen Asn-Gly-Arg (NGR) motif in platelet function - Moriarty, Róisín; McManus, Ciara A.; Lambert, Matthew; Tilley, Thea; Devocelle, Marc; Brennan, Marian; Kerrigan, Steven W.; Cox, Dermot (Thrombosis and Haemostasis, 2015)
The integrin αIIbβ3 on resting platelets can bind to immobilised fibrinogen resulting in platelet spreading and activation but requires activation to bind to soluble fibrinogen. αIIbβ3 is known to interact with the general integrin-recognition motif RGD (arginine–glycine–aspartate) as well as the fibrinogen-specific γ-chain dodecapeptide; however, it is not known how fibrinogen binding triggers platelet activation. NGR (asparagine–glycine–arginine) is another integrin-recognition sequence present in fibrinogen and this study aims to determine if it plays a role in the interaction between fibrinogen and αIIbβ3. NGR-containing peptides inhibited resting platelet adhesion to fibrinogen with an IC50 of 175 μM but failed to inhibit the adhesion of activated platelets to fibrinogen (IC50 > 500 μM). Resting platelet adhesion to mutant fibrinogens lacking the NGR sequences was reduced compared to normal fibrinogen under both static and shear conditions (200 s-1). However, pre-activated platelets were able to fully spread on all types of fibrinogen. Thus, the NGR motif in fibrinogen is the site that is primarily responsible for the interaction with resting αIIbβ3 and is responsible for triggering platelet activation.
Keywords: Platelets; GPIIb-IIIa; fibrinogen; platelet activation